Uma análise sistêmica das práticas de gestão do conhecimento, em uma empresa pública: estudo de caso no INMETRO - Passaes, Alexandre dos Reis Gonçalves (2009)
Knowledge currently occupies a prominent position in organizations and, for its importance in defining new ways of designing products or processes, must be treated appropriately. This study aims to examine the practices related to Knowledge Management (KM) in a public organization, through a case study in Inmetro, institution which, owing to its importance in metrological scene, requires alignment with business models compatible with the needs of the current organizational environment. Thus, this research involved a literature review on the topic and use of a questionnaire, in the organization, in order to assess at what stage of implementation of KM it is, and how the KM initiatives are reflected in its performance. The data helped in the preparation of proposed approach to the subject and may help in formulating a policy to guide the KM actions in this area and even positively affect the production function "effectiveness" of the Institution